Characterization of the microstructure and thermomechanical properties of invar 36 coatings deposited by HVOF and cold gas processes - Tillmann, W.; Khalil, O.; Baumann, I. (Technische Universität Dortmund, 2022)
The effect of impact velocity and temperature of invar particles deposited by high-velocity oxygen fuel (HVOF) and cold spray processes on the microstructure and oxidation content of invar coatings is not fully understood. Additionally, the effect of coating thickness on the coefficient of thermal expansion (CTE) of the coated material and the influence of cold working on the coating hardness are also insufficiently investigated. In the present study, invar coatings were deposited at temperatures close to and below the melting point of invar particles to maintain low CTE. It was found that particle impact temperature and velocity strongly affect pore formation and cohesiveness but slightly affect the hardness of invar coatings. Higher particle impact velocities with impact temperatures close to the invar’s melting point enhance highly the cohesiveness of HVOF-invar coatings. Furthermore, invar coatings stabilize the CTE of the coated material up to a temperature of 227 °C. An increment in the coating’s thickness of 150 µm leads to reducing the CTE of the coated material (Al) in the in-plane direction by 7.65%. Applying cold working using 200 kN compression increases the hardness of the treated coatings by 6% while machine hammer peening (MHP) has a slight effect.
Journal of thermal spray technology;31(8)
Keywords: Cold spray (CS); Coefficient of thermal expansion (CTE); High-velocity oxygen-fuel (HVOF); Invar effect; Machine hammer peening (MHP); Microhardness; 620; 670; Kaltspritzen; Wärmeausdehnung; Hochgeschwindigkeitsflammspritzen; Invar-Legierung; Beschichtung; Maschinelles Oberflächenhämmern; Mikrohärte